1990
DOI: 10.1016/1010-7940(90)90207-g
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for development of accelerated coronary artery disease in cardiac transplant recipients

Abstract: Allograft coronary artery disease (CAD) is the major determinant of long-term survival following heart transplantation (HTx). In a group of 210 heart transplant recipients, we diagnosed CAD in 54 (27.1%) by coronary angiography, postmortem examination or examination of the transplanted heart at the time of retransplantation. Retrospective analysis of potential risk factors for the development of CAD was performed for both immunological (rejection pattern, immunosuppressive therapy, cytomegalovirus [CMV] infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 6 publications
4
52
1
Order By: Relevance
“…Uretsky et al 15 have found a relation between allograft vasculopathy and the occurrence of two or more rejection episodes. These data were corroborated by Radovancevic et al 20 when they analyzed the experience of the Texas Heart Institute; these results, however, were not confirmed by data of other study groups such as the one by Gao et al 21 at Stanford University. In the present series, we have found no statistically significant difference between the group with allograft vasculopathy and the group with a normal coronary angiography in regard to the number of rejection episodes.…”
Section: Discussionsupporting
confidence: 77%
“…Uretsky et al 15 have found a relation between allograft vasculopathy and the occurrence of two or more rejection episodes. These data were corroborated by Radovancevic et al 20 when they analyzed the experience of the Texas Heart Institute; these results, however, were not confirmed by data of other study groups such as the one by Gao et al 21 at Stanford University. In the present series, we have found no statistically significant difference between the group with allograft vasculopathy and the group with a normal coronary angiography in regard to the number of rejection episodes.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore for this population, weight loss should be mandatory before listing for HT. Other comorbidity includes cirrhosis, peripheral vascular disease, addictions (tabacco, excessive alcohol) [52]. Psychosocial evaluation is mandatory before listing-up for HT.…”
Section: Heart Transplantation and Heart Failurementioning
confidence: 99%
“…CRT also has led to a degree of improvement in left ventricular volume and EF in patients with mild heart failure similar to that in patients with severe heart failure [34]. CRT reduced mortality and hospitalizations among asymptomatic or mildly symptomatic heart failure patients [52]. Hence, recent clinical trials are directed toward focus on delaying progression of heart failure in asymptomatic or less symptomatic patients.…”
Section: Non-drug Treatment and Heart Failurementioning
confidence: 99%
“…Corticosteroids and CNIs are the cornerstone of immunosuppressive therapy in heart transplant recipients [108][109][110]. These immunosuppressive agents used in routine post cardiac transplant care have deleterious effects on blood pressure [104,[109][110][111]. Introduction of CNIs shifted the paradigm of solid organ transplant.…”
Section: Hypertensionmentioning
confidence: 99%
“…Post-transplant hypertension plays a significant role in the onset of angiographic CAV. Hypertension in cardiac transplant recipients is multifactorial and various mechanisms are implicated in the genesis of hypertension [102][103][104][105][106][107]. The pathogenesis of hypertension in heart transplant recipients is multifactorial and complex.…”
Section: Hypertensionmentioning
confidence: 99%